Improving Child Outcomes and Quality in Early Childhood Education and Care Through Implementation of Professional Development: A Meta-Systematic Literature Review of Pre- and In-Service Approaches - Deding, Jesper; Minnaert, Alexander (Advances in Social Sciences Research Journal, 2024)
This systematic literature review explores the developing landscape of Early Childhood Education and Care (ECEC), highlighting its growing significance in contemporary society. It examines the complex dimensions of ECEC quality and its impact on children, with a particular focus on the critical role of staff education and training. Additionally, it reviews various tools and methods used to measure ECEC quality, framing the analysis around enhancing quality through comprehensive professional development (PD) initiatives. By conducting a meta-systematic literature review of meta-analyses and systematic reviews, this study synthesizes the characteristics and effects of both pre-service and in-service professional development for ECEC staff. Data extraction and cross-sectional analyses aim to identify patterns and differences in findings, ultimately informing effective PD strategies. The results show promising effects of in-service PD, particularly evidence-based practices such as coaching and mentoring, in improving educator practices and benefiting children's outcomes. Pre-service PD demonstrates positive, though varied, associations between educator qualifications and child outcomes, highlighting the need for policy interventions to improve staff education programs and raise ECEC quality. However, differences in international contexts and the diverse aims of outcomes limit generalizability. Factors such as duration, intensity, and alignment with targeted outcomes remain crucial for success. Tailored, collaborative, and context-specific PD interventions are recommended to enhance ECEC practices and child outcomes. Some PD elements, both pre- and in-service, show greater impact than others, suggesting that further research is necessary to refine approaches and clarify the variability in effects.